Corrosion inhibition of nickel in 4% nitric acid by substituted thione compounds - Kumar A.; Patnaik S.K.; Singh M.M. (My University, 2025)
The inhibition efficiencies of substituted thiones have been determined in 4% nitric acid in relation to the corrosion of nickel at different temperatures (25, 35 and 45°C) using a potentiostatic technique. All the investigated inhibitors are able to suppress appreciably the corrosion of nickel in the present system. 2-benzylmercapto-1-0-methoxy-4-phenyl-1,6-dihydro 1,3,5 triazine-6-thione is found to be the most effective inhibitor, followed by 2-benzylmercapto-1-0-methyl phenyl-1,6-dihydro 1,3,5 triazine-6-thione, 2-benzylmercapto-1,4-diphenyl-1,6-dihydro 1,3,5 triazine-6-thione and 2-benzylmercapto-1-0-chlorophenyl-4-phenyl-1,6-dihydro 1,3,5 triazine-6-thione. The inhibition efficiencies of the inhibitors are determined by the electrochemical technique and potential decay experiments are carried out to determine the relative stability of the passive film formed on the nickel surface in the presence and absence of inhibitor. © 1998 Elsevier Science S.A. All rights reserved.